A mixed-methods assessment of the Australasian Society of Genetic Counselors (ASGC) Mentor Program - Holly Canton; Rebecca Macintosh; Joanna Sweeting; Helen Mountain; Jodie Ingles; Amy Nisselle; Erin Turbitt; Alison McEwen; Laura Yeates (Genetics in Medicine Open)
Purpose: In Australia and New Zealand, one third of genetic counselors have less than 5 years’ experience. Sharing experienced practitioners’ professional knowledge is needed as the profession grows. Formal mentoring is an important facilitator of career progression and shared knowledge. In 2022, the Australasian Society of Genetic Counselors developed a 6-month mentor program, matching mentees with experienced genetic counselors (>10 years). We aimed to evaluate and assess the overall satisfaction and acceptability of the program, the matching process, and barriers to participation. Methods: We used an explanatory mixed-method design with cross-sectional surveys deployed at baseline and follow-up and opt-in semi-structured interviews. Interview transcripts were analyzed using codebook thematic analysis, and data were integrated in a narrative approach. Results: Fifteen mentors and 15 mentees (N = 30) from 17 dyads were included in the analysis (response rate 83%). Eighteen completed the postprogram survey, and 12 were interviewed. The majority were female (93%), European (90%), and worked clinically in public hospitals (63%). Mentors’ main reason for participating was “to give back to the next generation,” whereas mentees sought “help with career progression.” Time was a barrier to participating. The majority (89%) achieved their goals, and all participants would recommend the program. Most (61%) found the mentor/mentee matching to be excellent, and 44% believed they would continue the relationship after the program. Conclusion: The Australasian Society of Genetic Counselors Mentor Program filled a gap in professional development within the Australian and New Zealand genetic counseling community and highlighted a general desire to share knowledge with new members of the profession.